CPT in Antarctica - McCallum, A B (Australian Geomechanics Society, 2013)
CPT is used extensively to determine material properties in soils and clays, however, it has not previously been used in hard polar snow. Therefore, existing CPT equipment was adapted for use in Antarctica to assess polar snow to depths of 10 m or more where resistances may exceed 10 MPa. Snow is a rate dependant material and numerous factors must be considered when interpreting CPT in polar snow, but valuable parameters such as snow shear strength, stratigraphy and relative density may be obtained using CPT in polar snow.